Expression and Function of Granzymes A and B in Escherichia coli Peritonitis and Sepsis - M. Isabel García-Laorden; Ingrid Stroo; Sanne Terpstra; Sandrine Florquin; Jan Paul Medema; Cornelis van´t Veer; Alex F. de Vos; Tom van der Poll (Hindawi Limited, 2017)
Escherichia (E.) coli is the most common causative pathogen in peritonitis, the second most common cause of sepsis. Granzymes (gzms) are serine proteases traditionally implicated in cytotoxicity and, more recently, in the inflammatory response. We here sought to investigate the role of gzms in the host response to E. coli-induced peritonitis and sepsis in vivo. For this purpose, we used a murine model of E. coli intraperitoneal infection, resembling the clinical condition commonly associated with septic peritonitis by this bacterium, in wild-type and gzmA-deficient (gzmA−/−), gzmB−/−, and gzmAxB−/−mice. GzmA and gzmB were predominantly expressed by natural killer cells, and during abdominal sepsis, the percentage of these cells expressing gzms in peritoneal lavage fluid decreased, while the amount of expression in the gzm+ cells increased. Deficiency of gzmA and/or gzmB was associated with increased bacterial loads, especially in the case of gzmB at the primary site of infection at late stage sepsis. While gzm deficiency did not impact neutrophil recruitment into the abdominal cavity, it was accompanied by enhanced nucleosome release at the primary site of infection, earlier hepatic necrosis, and more renal dysfunction. These results suggest that gzms influence bacterial growth and the host inflammatory response during abdominal sepsis caused by E. coli.